Factors Related to Efforts to Prevent Child Marriage in Adolescents in Senior High Schools and Vocational High Schools in District X, Sintang Regency - Ya’ Afif Kurniawan; Agus Samsudrajat; Eka Hariani; Dian Indahwati Hapsari (Indonesian Journal of Administration and Health Research (IJAHR), 2025)
Child marriage is a complex problem that can increase maternal and infant mortality rates. Based on KUA data from District X, child marriage cases continue to increase in 2021 there were 75 cases, in 2022 to 101 and continued to increase in 2023 to 125 cases. The purpose of this study is to determine the factors related to efforts to prevent child marriage among adolescents in high schools and vocational schools in District X, Sintang Regency. This study uses a quantitative method with a cross-sectional approach. The population in this study was 1,167 with a sample of 285 male and female students taken using a random sampling technique. The results of the statistical test analysis used were the chi-square test. Data analysis used univariate and bivariate analysis. Based on the results of the study, there is a relationship between attitudes (p-value 0.026), family income (p-value 0.028), peer influence (p-value 0.001), media exposure (p-value 0.005), family roles (p-value 0.001) and there is no relationship between knowledge (p-value 0.076) with efforts to prevent child marriage in adolescents in high schools and vocational schools in X District, Sintang Regency. There is a need for cross-sector collaboration to prevent students from realizing the dangers of marriage at a young age.Perkawinan anak merupakan masalah kompleks yang dapat meningkatkan angka kematian ibu dan bayi. Berdasarkan Data KUA Kecamatan X kasus perkawinan anak terus meningkat pada tahun 2021 terdapat 75 kasus, tahun 2022 menjadi 101 dan terus meningkat pada tahun 2023 menjadi 125 kasus. Tujuan penelitian ini mengetahui faktor yang berhubungan dengan upaya pencegahan perkawinan anak pada remaja di SMA dan SMK Kecamatan X Kabupaten Sintang. penelitian ini menggunakn metode kuantitatif dengan pendekatan cross sectional. Populasi dalam penelitian ini sebanyak 1.167 dengan sample 285 siswa dan siswi yang di ambil dengan teknik random sampling. Hasi analisis uji statistik yang digunakan adalah uji chi-square. Analisis data menggukan analisis univariate dan bivariate. Berdasarkan hasil penelitian terdapat hubungan antara sikap (p-value 0,026), pendapatan keluarga (p-value 0,028), pengaruh teman sebaya (p-value 0,001), paparan media (p-value 0,005), peran keluarga (p-value 0,001) dan tidak terdapat hubungan antara pengetahuan (p-value 0,076) dengan upaya pencegahan perkawinan anak pada remaja di SMA dan SMK Kecamatan X Kabupaten Sintang. Perlunya kerjasama antar lintas sector untuk mencegah agar peserta didik dapat menyadari bahayanya menikah pada usia anak.